Long-term outcomes of pure olive oil to prevent postoperative peritoneal adhesions in rats - Altıntaş Ural, Dilan; Saruhan, Haluk; Saygın, İsmail and Altıntaş Aykan, Duygun and Ural, Alper and İmamoğlu, Mustafa (Journal of Surgery and Medicine, 2019)
Aim: Postoperative peritoneal adhesion (PPA) that occur after abdominopelvic surgery are the current problems of surgeons. The aim of this study was to investigate the effect of pure olive oil in preventing PPA. Methods: Thirty-two rats were randomly divided into four groups: (1) Sham group: 5 ml pure olive oil was injected percutaneously into the peritoneal cavity without laparotomy, (2) Adhesion group: A standard adhesion model was formed on jejunum, ileum and caecum. (3) Adhesion + olive oil: A standard adhesion model was formed on jejunum, ileum and caecum. Subsequently the area on jejunum, ileum and caecum was covered with 5 ml of pure olive oil. (4) Olive oil + adhesion: The area on jejunum, ileum and caecum was covered with 5 ml of pure olive oil. Subsequently the standard adhesion model was formed on this area. Four weeks later, abdominal cavities of rats were examined for PPA, using Evan’s adhesion classification and Zühlke’s histopathological grade scales. Results: PPA was not found in Group 1 in which olive oil was injected intraperitoneally. PPA was present in all rats in Group 2. Microscopic adhesion scores in Group 3 and 4 were significantly lower than Group 2. The collagen fiber fractions were significantly lower and there was a significant decrease in fibrosis. There was no statistically significant difference in microscopic adhesion scores in Group 3 compared to Group 4. Conclusion: We found that antiinflammation, tissue regeneration and hydroflotation effect of pure olive oil decreased PPA formation in rats by maintaining a long lasting effect on the wounded peritoneal surface. Thus olive oil, a cheap and easy to obtain product, can be used in cases of PPA in surgery clinics.